STRATEGI MENGEMBANGKAN KOMPETENSI PROFESIONALISME GURU PAI UNTUK MENYIAPKAN PEMBELAJARAN YANG BERMUTU - Moh. Faizin; Mochamad Fachrul Afiq; Ristya Rini (IAIN Pontianak, 2023)
This article describes strategies to develop the professional competence of PAI educators or teachers to prepare a quality teaching and learning process (quality). People who play a big role in education are teachers or educators. Indonesia has higher teacher education which creates graduates to become quality educators, transmitting knowledge to students. Thus, when on duty, teachers must have professional competence and attitude in teaching students. Professional teacher competencies are the kinds of skills needed to make you a professional teacher. While quality learning is a series of learning activities that make learning not difficult, not boring, enthusiastic, and able to achieve the desired goals of the teaching and learning process. In the teaching and learning process, teachers need to be trained to develop professional competencies in order to improve the quality of learning. The teacher's professionalism development strategy to achieve the goal of quality or quality learning includes: Always providing examples of personality values, understanding the pedagogical foundations and developing competency skills and skills, designing and making developments on learning practice tools, mastering and implementing teaching and learning process programs, have an academic minimum of Diploma IV or Bachelor's Degree, change the paradigm of bureaucracy, and carry out research.